Ordering in Nematogenic p-n-Heptyloxy Benzoic Acid-A Computational Study - Sahaya Baskaran, G.; Lakshmi Praveen, P.; P. Ojha, Durga (Asian Journal of Chemistry, 2010)
A computational study of ordering in p-n-heptyloxy benzoic acid (7OBAC) has been carried out with respect to translatory and orientational motions. The evaluation of atomic net charges and dipole moments at each atomic center has been carried out using the complete neglect differential overlap (CNDO/2) method. The modified Rayleigh-Schrodinegr perturbation theory along with a multicentered-multipole expansion method has been employed to evaluate long-range intermole-cular interactions, while a 6-exp potential function has been assumed for short-range interactions. Various possible geometrical arrangements between a molecular pair during different modes of interactions have been considered. A comparative picture of molecular parameters, such as total energy, binding energy and total dipole moment of 7OBAC with 8OBAC (p-n-octyloxy benzoic acid) and 9OBAC (p-n-nonyloxy benzoic acid) has been given. An attempt has been made to analyze the nematogenic behaviour of 7OBAC at molecular level and develop a simple model by building in realistic features